2014
DOI: 10.1186/bcr3662
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at CYP3A is associated with age at menarche and breast cancer risk: a case-control study

Abstract: IntroductionWe have previously shown that a tag single nucleotide polymorphism (rs10235235), which maps to the CYP3A locus (7q22.1), was associated with a reduction in premenopausal urinary estrone glucuronide levels and a modest reduction in risk of breast cancer in women age ≤50 years.MethodsWe further investigated the association of rs10235235 with breast cancer risk in a large case control study of 47,346 cases and 47,570 controls from 52 studies participating in the Breast Cancer Association Consortium. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Additionally, many large genome-wide studies have found links between LIN28B and menarche (6-8, 10, 15, 64). Importantly, genetic loci that influence the age of menarche and age of thelarche often also impact breast cancer risk in women (15,(33)(34)(35)(36). These studies underscore the tremendous complexity of the regulation of puberty timing and the pleiotropy and environmental interactions that likely exist between menarche, body fat, and several diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many large genome-wide studies have found links between LIN28B and menarche (6-8, 10, 15, 64). Importantly, genetic loci that influence the age of menarche and age of thelarche often also impact breast cancer risk in women (15,(33)(34)(35)(36). These studies underscore the tremendous complexity of the regulation of puberty timing and the pleiotropy and environmental interactions that likely exist between menarche, body fat, and several diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does the reproductive lifespan's timing and length relate to female fertility, but the lifespan itself is closely associated with risks for various diseases and cancers. Notably, many genetic and epidemiologic studies have found that earlier menarche is linked with great risks for obesity (11,(20)(21)(22)(23)(24)(25)(26)(27), type 2 diabetes mellitus or insulin resistance (2,28,29), cardiovascular disease and mortality (2,29,30), and various cancers, including endometrial cancer (14,31) and breast cancer (14,15,(32)(33)(34)(35)(36). Conversely, later age of menarche is linked with increased risk for osteoporosis, decreased fertility, and decreased risk for breast and endometrial cancer, type 2 diabetes, and obesity (2,29,37).…”
mentioning
confidence: 99%
“…We thank the Breast Cancer Association Consortium (BCAC) for access to the data published in Johnson et al 15 …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Out of the 182 genetic loci associated with breast cancer in GWAS, 11 no one was located in XM genes. Breast cancer risk in relation to XM gene polymorphisms has been investigated in NATs, 12 CYPs, [13][14][15] GSTs, 16 UGTs, 17,18 SULTs, 19,20 but in these studies breast cancer risk was investigated in relation to individual SNPs without consideration of their possible joint effects. Studies on NAT1 and NAT2 genes have assessed breast cancer risk in relation to specific combinations of SNPs to characterize the acetylator phenotype (slow, intermediate or rapid).…”
Section: Introductionmentioning
confidence: 99%